Individual and shared representations on "zones calmes" ("quiet areas") among the French population in urban context. (1st December 2015) - Lavandier, Catherine; Delaitre, Pauline
Abstract: Since the European directive 2002/49/EC, European cities of more than 100, 000 inhabitants have had to define quiet areas. To take into account the feelings of inhabitants, some cities have conducted questionnaires in-situ or workshops. These methods allow giving local definitions of quiet areas. In this paper, another approach has been tested, known as Q-methodology. This method makes it possible to reveal the representations shared by people who have similar attitudes related to life experience. Through an online survey, 302 participants were asked to rank 47 sentences which describe opinions about quiet areas with a Likert scale going from −5, "most disagree" to +5, "most agree". A Principal Component Analysis was conducted and the selected factors were interpreted with the exclusive contributors of each group. Three main groups can be characterized by (1) the need for social relationships, (2) the need for nature, and (3) the need for silence. Some less important groups focus on the need for safety and the rejection of children. These different representations can be a challenge for French cities which choose to promote diversity and try to imagine how to satisfy, in a same location, all types of people.